Analisis Konseptual Evolusi Teori Organisasi Klasik hingga Modern: Sebuah Studi Pustaka - Puput Aryani (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
The study of organizational theory plays an essential role in understanding the dynamics of organizational management across different eras. This article discusses the evolution of organizational theory, beginning with classical theory, followed by neo-classical theory, and culminating in modern organizational theory along with its implications for contemporary management. Classical organizational theory emerged in the late 19th and early 20th centuries in response to the demands for work efficiency during the Industrial Revolution. Key figures such as Frederick W. Taylor, Henri Fayol, and Max Weber emphasized formal structures, clear hierarchies, and standardized work procedures. Over time, weaknesses in the classical approach—particularly its neglect of social and psychological aspects—led to the rise of neo-classical theory, which placed human factors at the center of organizational success through behavioral approaches. Thinkers like Elton Mayo, Chester I. Barnard, Douglas McGregor, and Chris Argyris enriched this theory by focusing on motivation, communication, and social relations in the workplace. By the mid-20th century, modern organizational theory emerged with an open systems perspective, positioning organizations as entities actively interacting with their external environments. This theory emphasizes flexibility, adaptability, technological integration, and highlights concepts such as contingency theory, learning organizations, and transformational leadership. Through this conceptual study, it is concluded that organizational theories have evolved adaptively in line with social, economic, and technological developments. This article is expected to serve as a conceptual reference for academics and practitioners in understanding organizational management in the digital and globalization era.